Eric Voegelin’s Authoritarian State Against the Background of His Critique of Hans Kelsen’s Pure Theory of Law - Okoński, Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article refers to the issues presented in E. Voegelin’s The Authoritarian State: An Essey on the Problem of the Austrian State, which are important from the point of view of the theory and philosophy of law. Attention was paid to the criticism of H. Kelsen’s normativism and Voegelinʼs interpretation of the parliamentarism of the interwar Austria. This issue was placed against the background of the dispute over the Austrian state. The methodological aspect of the presented issue was especially taken into account. Some of the issues discussed were outlined against the background of the post-war works of E. Voegelin